(untitled) (Bangladesh Journal of Medical Science, 2015)
Background: Mycoplasma pneumonia (M. pneumoniae) is an important causative agent of childhood infection with variable clinical presentations. The objective of the study was to evaluate the laboratory investigation and antimicrobial therapy of M. pneumoniae infection in children admitted to paediatric ward. Materials & Methods: A total of 111 children, of which 59 (53.2%) boys and 52 (46.8%) girls, with median age of 2 years (inter quartile range 1-6 years) with suspected M. pneumoniae infection were tested for IgM by enzyme-linked immunosorbent assay (ELISA). The children were classified as seropositive and seronegative. Results: Of the 111 children, 45 (40.5%) had serological evidence of M. pneumoniae infection and the remaining 66 (59.5%) were seronegative. There was significant association (p < 0.001) between age and serology response. Seropositive children were more likely to be older (median age 5.0 [interquartile range 2- 7] years, p < 0.001). Children with M. pneumoniae infection were less likely to have cough (p = 0.023) in which 55 (65.5%) patients having cough were seronegative. There was no significant association between laboratory findings of full blood count and serology. Conclusion: In addition to clinical and laboratory features, other factors like age group and absence of cough might be helpful in predicting M. pneumoniae infection. DOI: http://dx.doi.org/10.3329/bjms.v14i1.21564 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.75-78